198k views
3 votes
What is the solution to the following equation? 4(3x − 6) + 15 = 27 2 3 4 5

User Hkm Sadek
by
5.7k points

2 Answers

4 votes

Answer:

3

Explanation:

User GPI
by
6.1k points
4 votes

Answer:

Hi there!

The answer to this question is 3

Explanation:

You first distribute the four into the parenthesis to get: 12x-24+15+ 27

Next you add -24 to 15 to get: -9 your equation should now look like 12x-9=27

Then you add 9 on both side to get 12x=36

Last you divide twelve on both sides to x=3

User Rukomoynikov
by
5.6k points